2006
DOI: 10.1016/j.theriogenology.2005.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis in the turkey (Meleagris gallopavo): Quantitative approach in immature and adult males subjected to various photoperiods

Abstract: The objectives of this study were to identify and quantitate the germ cell populations of the testes in sexually mature male turkeys (Trial 1), determine the duration of meiosis based on BrdU labeling and stereological analyses (Trial 2), and examine the impact of various photoperiods on germinal and somatic cell populations in immature and adult males (Trial 3). In Trial 1, both testes within a male had similar stereological components (P > 0.05) for all parameters analyzed. In Trial 2, the duration of Type-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
27
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 26 publications
8
27
0
6
Order By: Relevance
“…This confirmed previous reports that a strictly short photoperiod per se (7L or 8L/day) has a non-stimulatory effect on reproductive traits (fowl: [29,30]; turkey: [10,11]; guinea-fowl: [20]). By contrast, in male turkeys a moderate or even shorter photoperiod such as 10.5L:13.5D from 23 wk of age appeared to be stimulatory by 30-34 wk of age.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This confirmed previous reports that a strictly short photoperiod per se (7L or 8L/day) has a non-stimulatory effect on reproductive traits (fowl: [29,30]; turkey: [10,11]; guinea-fowl: [20]). By contrast, in male turkeys a moderate or even shorter photoperiod such as 10.5L:13.5D from 23 wk of age appeared to be stimulatory by 30-34 wk of age.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies using commercial breeder turkeys revealed a high degree of sensitivity to photoperiod for TW [10,11], semen output [18], and circulating LH and testosterone concentrations [6][7][8][9]. The present results confirmed previous observations [10,11] that prepubertal male turkeys maintained under constant long days are precocious semen producers (26-29 wk) In . Each point represents the mean AE S.E.M.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another specific feature of reproduction in males of avian species is the relatively short interval of time required for B-type spermatogonia to evolve into spermatozoa compared with mammals. For example, in the chicken, guinea-fowl, duck and turkey, the duration of spermatogenesis is approximately 14 days (De Reviers, 1968;Marchand et al, 1977;Brillard, 1981;Noirault et al, 2006), which provides males with extended potential to produce large quantities of gametes within a given period of time. Following their evacuation from the rete testis, avian sperm are rapidly transported through the epididymis to the vas deferens, where they are stored for a limited period of time (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A morphological description of the various cell categories involved in the processes of avian spermatogenesis has already been proposed in several species (Zhao et al, 2002;Siu et al, 2004;Brillard 1986;Lin and Jones, 1990;Thurston et al, 2000;Goes and Dolder, 2002;Noirault et al, 2006) but the identification of stem spermatogonia on the basis of cell surface markers has been achieved only recently (Bakst et al, 2007). The precise identification of germinal stem cell populations, particularly that of spermatogonial stem cells, might be very helpful for efficient and reproducible transplantation and repopulation of recipient seminiferous epithelium.…”
mentioning
confidence: 99%